The hero-warrior in the worldview and practice of contemporary Pagans in Ukraine - Smorževsʹka, Oksana Oleksandrivna ca. 20./21. Jh. (Religio, 2023)
Russia's military aggression against Ukraine has actualized the ideological Native Faith understanding of the role of the warrior, and his sacred duty as a defender of his native land and his ideals. For a Ukrainian Native Faith adherent (a Ridnovir), a warrior is not merely a person with a weapon in his hands who is serving in the military. The image of the warrior is closely intertwined both with historical events and persons, and with mythic and poetic images, primarily from Slavic and Scandinavian mythology. This forms a romantic image of a brave warrior-hero who is called by higher forces (Perun, Matir-Slava, Odin, the Valkyries) to defend his native land and to be happy to die for it. A special place belongs to Taras Shevchenko, a spiritual warrior whose weapon was the word. Relying on one's religious beliefs and worldview in order to interpret selected events in the history of Ukraine (the life of Prince Svyatoslav the Brave, the Cossack era, the struggles of the UIA) is an excellent ideological foundation for maintaining the fighting spirit and substantiating the tradition. Among the Ridnovirs who have died defending Ukraine's freedom, we may pick out the examples of Serhiy Tabala, Anton Tsedik and Serhiy Zaikovsky.